The Influence of Self Esteem, Empowerment, and Work Flexibility on Employee Performance at PT. PLN (Persero) UP3 Sukoharjo - Dewi, Enris Salia; Hikmah, Khoirul (CV. Strata Persada Academia, 2025)
This study aims to determine and analyze the effect of self esteem, empowerment, and work flexibility on the performance of employees of PT. PLN (Persero) UP3 Sukoharjo. Data in this study were taken using a quantitative approach with data collection through a questionnaire. This research uses primary data type and Likert scale as the measurement scale. Respondent in this research are all employees of PT. PLN (Persero) UP3 Sukoharjo with a total of 59 respondent. The method for the analysis of this human resources represent a pivotal asset that ought to be given due consideration was done by using multiple linear regression analysis with SPSS software. The results of this study indicate that self esteem, empowerment, and work flexibility affect employee performance partially and collectively. Empowerment has the largest beta coefficient variable (0,387), followed by self esteem (0,383) and work flexibility (0,230). The F-test shows the collectively influence of the variables of this study, with an F-statistic of 46,722 and a sig value of 0,000 indicating a positive and significant influence. The results of this study indicate the important role of self-esteem, empowerment, and work flexibility in improving employee performance. It is recommended for PT. PLN (Persero) UP3 Sukoharjo to focus on increasing self-esteem, empowerment, and work flexibility because this can improve overall employee performance.